Experimental validation of the Newton observer for a nonlinear flux-controlled AMB system operated with zero-bias flux. Issue 9 (1st September 2020) - Mystkowski, A.; Kierdelewicz, A.; Kotta, Ü.; Kaparin, V.
ABSTRACT: The paper presents the results of experimental validation of the Newton observer for estimation of the magnetic flux within the feedback control of a nonlinear active magnetic bearing (AMB) system. In the preliminary work the Newton observer was adapted for the exact discrete-time model of the simplified one-degree-of-freedom AMB system, operated with zero-bias flux and under the voltage switching strategy, and showed good results in case of numerical simulations. The objective of this paper is to confirm these results on the basis of experimentation. The experiments were conducted on the AMB test rig, developed and manufactured at Bialystok University of Technology.